Efektivitas Peraturan Daerah Kabupaten Klungkung No.7 Tahun 2014 tentang Pengelolaan Sampah - I Kadek Wisnu Dwipayana Ariska; I Ketut Sukadana; Diah Gayatri Sudibya (Warmadewa Press, 2021)
One of the cities in Bali Province, Klungkung Regency; is one of the districts in Bali which is very developed in the arts and small industry, but has a problem, namely waste. This study aims to analyze the implementation process and analyze the actions of the local government regulations of Klungkung Regency No. 7/2014 on the people of Klungkung Regency. The research method used is empirical research. In carrying out this research, researchers went directly to the field and directly examined what was happening in the real field. The results showed that the government, which has full authority on waste management, must protect the community so that it can be managed properly and properly, not littering. Through this research, it is hoped that the Klungkung Regency Government will increase community participation in proper and correct waste management.